Coffee husk as feldspar substitute in the manufacture of enameled ceramic tile (2020)
This study researches the effect of adding coffee husk (ch) and coffee husk ash (cha) as partial feldspar substitutes to the manufacture of enameled ceramic tiles. Clays and other paste additives were characterized using xrd and xrf. The designed prototypes were pressed, dried, and fired at 1,120 °C. The physical (drying and firing shrinkage, apparent density, water absorption) and mechanical (flexion resistance) properties were evaluated and compared with standard fired specimens. Although the physical and mechanical properties of the specimens with 5 and 10 % ch and cha make them suitable for the manufacture of biib ceramic tiles, it was concluded that ch and cha under the working conditions do not replace feldspar in the preparation of enameled ceramic tiles due to surface quality defects